What's the Damage? : Medium-term Output Dynamics After Banking Crises - Abiad, Abdul (IMF Working Papers; Working Paper ;, 2009)
This paper investigates the medium-term behavior of output following banking crises, and its association with pre- and post-crisis conditions and policies. We find that output tends to be depressed substantially following banking crises, with no rebound to the precrisis trend. However, growth does eventually tend to return to its precrisis rate, with substantial crosscountry variation in outcomes. The depressed path of output typically results from reductions of roughly equal proportions in the employment rate, the capital-to-labor ratio, and total factor productivity. Initial conditions that are strongly associated with medium-run output losses include the short-run change in output, the occurrence of a joint banking-and-currency crisis, and a high precrisis level of investment. Short-run fiscal and monetary stimulus is associated with smaller medium-run deviations of output and growth from the precrisis trend.